The Transformation of Spanish Photojournalism during Transition: Comparative study between El País, ABC and La Voz de Galicia - Del Campo Cañizares, Elpidio; Spinelli Capel, Leónidas (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper aims to observe the transformation of photojournalism along Spanish Transition through a comparative analysis between two national newspapers: El País and ABC and a regional one: La Voz de Galicia. Try to check to what extent the trend pointed by El País was followed by the rest of the newspapers. It uses a sample of relevant news and is complemented by an interview with the photojournalist from La Voz de Galicia Xosé Castro.Results show that El País, from the beginning, establishes new paradigms in photojournalism; but these are not followed by the other newspapers.